Enhancing customer perception and satisfaction: factors influencing customer service quality towards takaful insurance at Etiqa Takaful Berhad Temerloh / Farah Adibah Abdul Razak - Abdul Razak, Farah Adibah (Faculty of Business and Management, 2010)
This study is prepared in order to finish my study in Bachelor of Business Administration (Hons) Marketing. I choose to study about “Enhancing Customer Perception and Satisfaction: Factors Influence Customer Service Quality towards Takaful Insurance at Etiqa Takaful Berhad Temerloh Branch”. This project paper contains of five chapters. It includes an introduction, literature review, research methodology and design, data analysis and interpretation and conclusion and recommendation. The purpose of this study is to identify the best factors that influence customer service quality towards Takaful insurance at Etiqa Takaful Berhad Temerloh and also to identify the level of customer service quality provided by Etiqa Takaful Berhad Temerloh. This study was conducted throughout the duration of five month practical training. The study generated full response rate from 40 respondents (customers) who are currently come Etiqa Takaful Berhad Temerloh for services. All the responses from the questionnaires given to the respondents were statistically analyzed with several statistically tool by using SPSS version 11.5. From the analysis, there are few output that researcher get in terms of reliability analysis, frequency distributions, descriptive statistics, Pearson’s Correlation Coefficient and also Linear Regression.